PENGARUH EKUITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP PERTUMBUHAN LABA PERUSAHAAN DI BURSA EFEK INDONESIA - Sunarto wage; Baru Harahap (LPPM Universitas Putera Batam, 2022)
This study aims to analyze and determine the effect of equity, profitability, and leverage on profit growth in companies listed on the Indonesia Stock Exchange (IDX). The financial ratios used consist of ROE, ROA, and DER. The sampling technique used purposive sampling method. The data used in this study is secondary data, namely financial statements published in the first quarter of 2022. The data comes from 40 companies on the Stock Exchange. In this study, the analytical technique used is multiple linear regression analysis. Based on the results of simultaneous hypothesis testing, the independent variables together have no significant effect on profit growth, with the results of the coefficient of determination being 16%. Based on the results of partial hypothesis testing, equity, profitability, and leverage have no effect on profit growth